2021
DOI: 10.1002/cam4.4301
|View full text |Cite
|
Sign up to set email alerts
|

SEC61G overexpression and DNA amplification correlates with prognosis and immune cell infiltration in head and neck squamous cell carcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Sec61 translocon gamma subunit (SEC61G) protein is over-expressed in different kinds of cancer and enhances tumor cell growth [ 31 ]. Silencing of this protein blocks AKT survival signaling, thus, playing an anticancer role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sec61 translocon gamma subunit (SEC61G) protein is over-expressed in different kinds of cancer and enhances tumor cell growth [ 31 ]. Silencing of this protein blocks AKT survival signaling, thus, playing an anticancer role.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells show a high rate of proliferation, and SEC61G is one of the main genes involved, acting as proto-oncogene and enhancing cancer cell survival [ 44 , 47 ]. It is observed that by knocking it out, EGFR/AKT survival signaling, and tumor growth are inhibited [ 31 ]. To the best of our knowledge, no authors describe the interaction between SEC61G and the EC system, but in this study, we observe a reduction in the transcription of SEC61G after the selective stimulation of CB2, thus, suggesting a correlation between them.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in SEC61 alpha (SEC61A1) and gamma (SEC61G) subunits have been associated with disease. 4750 Altered SEC61A1 expression or function of SEC61A1 expression has been linked to diabetes mellitus, polycystic kidney disease, and immunodeficiency, whereas reduced SEC61A1 expression is associated with a decrease in ER calcium leak. 49,51,52 Increased SEC61G has been reported in multiple solid organ malignancies, and is thought to promote cancer development, progression, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…SEC61G was found to be overexpressed in BC and might co-amplify with epidermal growth factor receptor (EGFR) ( Reis-Filho et al, 2006 ). Lu et al reported that the expression of SEC61G in BC was negatively correlated with its promoter methylation ( Lu et al, 2021 ). In our research, similar trend could be found that the expression of SEC61G was negatively related with the methylation of cg00945507.…”
Section: Discussionmentioning
confidence: 99%